How to level the risk of bleeding while taking anticoagulant therapy in patients with atrial fibrillation? - Svetlana A. Berns; Olga L. Barbarash (ZAO "Consilium Medicum", 2022)
Atrial fibrillation (AF) is one of the most common types of cardiac arrhythmias, while AF is the main risk factor for ischemic stroke. For a long time, vitamin K antagonists, primarily warfarin, have been the standard for the prevention of thromboembolic complications in patients with AF. 5 years ago, dabigatran, rivaroxaban and apixaban occupied the 2nd place in the structure of anticoagulant prescribing (AC), giving way to warfarin. The well-known reason for the inadequate use of AC is the risk of bleeding. There are a large number of validated scales for assessing the risk of hemorrhagic complications, in particular HAS-BLED, ABC, HEMORRHR2HAGES, ATRIA, ORBIT, but the estimated high risk of bleeding should not be the only and absolute limitation to the appointment of AC. Despite the real risk of bleeding on the background of taking AC in patients with AF, an integrated approach taking into account not only the risk factors of the thromboembolic complications, but also hemorrhagic complications, with an emphasis on the existing comorbidities, the presence of comorbidity, old age, etc., will allow an individual approach to the choice of AC and its dose, contributing to the optimization of the management of such kind of patients.